Penerapan Klausula Force Majeure Akibat Keterlambatan Perizinan Ekspor: Studi Kasus PT Freeport Indonesia - Sylvania Okta Aurelia; Alvi Septia Listyani; Syaefwanda Agita Saputri; Rayi Kharisma Rajib (JURNAL ILMIAH NUSANTARA, 2026)
This article examines the application of the force majeure clause in PT Freeport Indonesia’s export contracts when delays in export permits arise from government actions. The study focuses on two central issues: whether such delays can be classified as force majeure, and how the clause is implemented within Freeport’s commodity contracts. Based on an analysis of contract law doctrine, the Indonesian Civil Code, and international commercial practices, the delay in export permits satisfies the elements of force majeure because it originates from government policies beyond the company’s control, is unforeseeable, unavoidable, and results in the temporary impossibility of performing delivery obligations. The contractual practices of Freeport further show that the force majeure clause is structured to anticipate government intervention through mechanisms such as formal notification, proof of non-negligence on the part of the company, and adjustments to delivery schedules once permits are reinstated. The findings confirm that the force majeure clause functions as an effective legal tool to protect Freeport and maintain the stability of international trade relations amid fluctuating mineral export regulations. This study highlights the need for more precise and adaptive drafting of force majeure clauses to address regulatory uncertainty in the mining sector.